PELAKSANAAN PENDAFTARAN TANAH ULAYAT KAUM MELALUI PROGRAM PENDAFTARAN TANAH SISTEMATIS LENGKAP DI KECAMATAN BUNGUS TELUK KABUNG - Feronika, Feronika; Fendri, Azmi; Mirwati, Yulia (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2019)
Ulayat land is a land that is acquired from generation to generation whose control and utilization are regulated by the Mamak Waris Head. This is all obtained without correspondence or in Writing, only by knowing the boundaries naturally with someone else's land. In Padang City, especially in Bungus Teluk Kabung Subdistrict, most of the existing property is customary land. Ulayat land is used for the benefit of its people. The government is obliged to hold land registration in the entire territory of the Republic of Indonesia. One of the methods adopted by the Ministry of Agrarian and Spatial Planning / National Land Agency is through the Complete Systematic Land Registration Implementation Acceleration program as stipulated in the Regulation of the Minister of Agrarian and Spatial Planning / Head of the Republic of Indonesia National Land Agency Number 12 of 2017 concerning Acceleration of Complete Systematic Land Registration , which was carried out in Bungus Teluk Kabung Subdistrict which had a target of 1,100 fields. The formulation of the problem in this Writing is 1. How is the implementation of community ulayat land registration through the Complete Systematic Land Registration program in Bungus Subdistrict Teluk Kabung. 2. What obstacles were encountered in the implementation of the record of communal ulayat land through the Complete Systematic Land Registration program in Bungus Subdistrict Teluk Kabung. And in this Writing, the author uses a sociological juridical approach. Based on the research conducted by the author, the implementation of the registration of ulayat land of the people through the Complete Systematic Land Registration Program in Bungus District Teluk Kabung. It is challenging to implement and does not achieve this target because there are some obstacles in the implementation of the ulayat land registration of the people so that the ulayat land of the community cannot be registered with the Land Office. Constraints arise include subject, namely whose name certificate recorded in the name of the Mamak Chief Heir, on behalf of one member of the community or in the name of Mamak the Head of Waris along with members of the city because in most fields many register on behalf of one member the people without being noticed by Mamak To Waris and other members of the people. Another obstacle is the absence of the Mamak Waris Head and Kerapatan Adat Nagari in the land registration process.